A Comparative Study of Meniscectomy and Nonoperative Treatment for Degenerative Horizontal Tears of the Medial Meniscus. (July 2013) - Yim, Ji-Hyeon; Seon, Jong-Keun; Song, Eun-Kyoo; Choi, Jun-Ik; Kim, Min-Cheol; Lee, Keun-Bae; Seo, Hyoung-Yeon
Background: It is still debated whether a degenerative horizontal tear of the medial meniscus should be treated with surgery. Hypothesis: The clinical outcomes of arthroscopic meniscectomy will be better than those of nonoperative treatment for a degenerative horizontal tear of the medial meniscus. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 102 patients with knee pain and a degenerative horizontal tear of the posterior horn of the medial meniscus on magnetic resonance imaging were included in this study between January 2007 and July 2009. The study included 81 female and 21 male patients with an average age of 53.8 years (range, 43-62 years). Fifty patients underwent arthroscopic meniscectomy (meniscectomy group), and 52 patients underwent nonoperative treatment with strengthening exercises (nonoperative group). Functional outcomes were compared using a visual analog scale (VAS) for pain, Lysholm knee score, Tegner activity scale, and patient subjective knee pain and satisfaction. Radiological evaluations were performed using the Kellgren-Lawrence classification to evaluate osteoarthritic changes. Results: In terms of clinical outcomes, meniscectomy did not provide better functional improvement than nonoperative treatment. At the final follow-up, the average VAS scores were 1.8 (range, 1-5) in the meniscectomy group and 1.7 (range, 1-4) in the nonoperative group ( P = .675). The average Lysholm knee scores at 2-year follow-up were 83.2 (range, 52-100) and 84.3 (range, 58-100) in the meniscectomy and nonoperative groups, respectively ( P = .237). In addition, the average Tegner activity scale and subjective satisfaction scores were not significantly different between the 2 groups. Although most patients initially had intense knee pain with mechanical symptoms, both groups reported a relief in knee pain, improved knee function, and a high level of satisfaction with treatment ( P < .05 for all values). Two patients in the meniscectomy group and 3 in the nonoperative group with Kellgren-Lawrence grade 1 progressed to grade 2 at the 2-year follow-up. Conclusion: There were no significant differences between arthroscopic meniscectomy and nonoperative management with strengthening exercises in terms of relief in knee pain, improved knee function, or increased satisfaction in patients after 2 years of follow-up.